2010
DOI: 10.1088/0953-8984/22/25/255602
|View full text |Cite
|
Sign up to set email alerts
|

Importance of conduction electron correlation in a Kondo lattice, Ce2CoSi3

Abstract: Kondo systems are usually described by the interaction of the correlation induced local moments with the highly itinerant conduction electrons. Here, we study the role of electron correlations among conduction electrons in the electronic structure of a Kondo lattice compound, Ce₂CoSi₃, using high resolution photoemission spectroscopy and ab initio band structure calculations, where Co 3d electrons contribute in the conduction band. High energy resolution employed in the measurements helped to reveal the signat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 43 publications
1
34
0
Order By: Relevance
“…However, the width (at half intensity) of the experimental photoemission peak is larger by about 0.4 eV than the calculated one, nearly independent of U. Similar approach was made in the case of Ce 2 CoSi 3 [41], where different parameters U were used for Ce(4f) and Co(3d) electrons.…”
Section: Type Of Dosmentioning
confidence: 55%
“…However, the width (at half intensity) of the experimental photoemission peak is larger by about 0.4 eV than the calculated one, nearly independent of U. Similar approach was made in the case of Ce 2 CoSi 3 [41], where different parameters U were used for Ce(4f) and Co(3d) electrons.…”
Section: Type Of Dosmentioning
confidence: 55%
“…[6][7][8] The valence band consists of Si 3p, Co 3d and Rh 4d electronic states. 9,10 Since the binding energy of the 4d electronic states is higher than the 3d electronic states and 3d electrons are relatively more correlated due to smaller radial extension, 11,12 the substitution of Co at Rh sites influences the effective d-p hybridization as well as the itineracy of the conduction electrons that leads to a plethora of interesting properties. For example, one of the end members, Ce 2 RhSi 3 exhibit antiferromagnetic ordering at about 7 K. studies involving lattice compression/expansion via external pressure or chemical substitutions suggested that this compound lies close to the peak of Doniachs magnetic phase diagram.…”
Section: Quantum Criticalitymentioning
confidence: 99%
“…A Kondo resonance feature called coherent feature appears at the Fermi level representing the itinerant electrons. The decrease in temperature leads to an increase in the coherent feature intensity at the cost of incoherent features [31,32]. While such increase in spectral intensity can have other origin, it is strongly felt [33] that the enhancement of the feature A with the decrease in temperature shown in figure 1c can be attributed to correlation-induced effects as justified later in the text.…”
Section: Kalobaran Maitimentioning
confidence: 97%